Analisis Harga Pokok Penjualan dan Cukai Rokok terhadap Net Profit Margin - Toruan, Hubert Mulya Sari Lumban; Veronica, Sienly (Jurnal Informatika Ekonomi Bisnis, 2024)
Cigarette excise increasement issue has an impact on companies net profit. The government policy has raised the cost of goods sold. Cigarette companies should decide to increase net profit. This research was designed with multilinear regression method to determine effect of the cost of goods sold and cigarette excise on net profit margin of cigarette companies which enlisted in Indonesia Stock Exchange for 2013–2022-year periods. The data set that used in this research are secondary data which consist of net sales, cost of goods sold, net income, and cigarette excise that taken from each company’s financial annual report. The result shows that cost of goods sold, and cigarette excise have negative effect on net profit margin in simultaneous impact. Partially, the cost of goods sold has a negative effect on net profit margin than cigarette excise. In this case, companies have to consider other aspects before making the cost of goods sold determination. This decision would have more effect on net profit margin than cigarette excise does.